Protective effects of caffeic acid phenethyl ester on iron-induced liver damage in rats - Oktar, S.; Yonden, Z.; Aydin, M.; Ilhan, S.; Alcin, E.; Ozturk, O. H. (Springer, 2009)
S. OKTAR, Z. YONDEN, M. AYDIN, S. ILHAN, E. ALCIN and O.H. OZTURK. Protective effects of caffeic acid phenethyl ester on iron-induced liver damage in rats. J Physiol Biochem, 65 (4), 339-344, 2009. Caffeic acid phenethyl ester (CAPE) is a natural product with potent anti-inflammatory, antitumor, and antioxidant activities, and attenuates inflammation and lipid peroxidation. The purpose of the present study was to investigate the effects of CAPE on iron-induced liver damage. Rats were divided into four groups and treated for 7 days with saline (control group), 10 mu mol kg CAPE/day s.c. (CAPE group), 50 mg iron-dextran/kg i.p. (IRON group) and CAPE and iron at the same time (IRON+CAPE group). Seven days later, rats were killed and the livers were excised for biochemical analysis. The administration of IRON alone resulted in higher myeloperoxidase (MPO) activity and lipid peroxidation than in the control and CAPE treatment prevented the increase in MPO activity and malondialdeyde (MDA) level. No differences were observed in all four groups with regards to superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT) activities. Our results collectively suggest that CAPE may be an available agent to protect the liver from injury via inhibition of MPO activity.
Keywords: Caffeic acid phenethyl ester; Iron overload; Myeloperoxidase; Malondialdehyde; Oxidative stress; Liver